1893
DOI: 10.1002/jmor.1050080104
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the lung

Abstract: THE difficulty in unraveling the various subdivisions of the bronchus of higher animals has made it impossible for us to gain a clear idea of the structure of the lung tissue. From a comparative standpoint it has also been impossible to gain light regarding the structure of the mammalian lung, mainly on account of the many variations in the different groups of animals. With these facts in view, I have attempted to rework the whole subject in question, guided by Dr. Mall and aided by a Fellowship granted by Cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1913
1913
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…The resistance to blood flow in the large conducting arteries and veins is not known, but an estimate can be made of the pressure drop across these vessels by using Poiseuille's law. Values for main pulmonary, artery, left pulmonary artery, and venous trunk diameter were taken from the measurements of Miller (18), and values for vessel length from the estimates of Schleier (1). At the average flow in our experiments the pressure drop across the main pulmonary artery would be 0.08 cm H2O and the pressure drop across the left pulmonary artery would be 0.12 cm H2O.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The resistance to blood flow in the large conducting arteries and veins is not known, but an estimate can be made of the pressure drop across these vessels by using Poiseuille's law. Values for main pulmonary, artery, left pulmonary artery, and venous trunk diameter were taken from the measurements of Miller (18), and values for vessel length from the estimates of Schleier (1). At the average flow in our experiments the pressure drop across the main pulmonary artery would be 0.08 cm H2O and the pressure drop across the left pulmonary artery would be 0.12 cm H2O.…”
Section: Resultsmentioning
confidence: 98%
“…Schleier made a detailed mathematical analysis of the distribution of vascular resistance in the human lung using Poiseuille's law. He employed Miller's measurements of vessel diameter (18) and assumed figures for vessel length in his calculations. He concluded that, in contrast to the systemic vascular bed where the muscular arterioles are the major resistance vessels, in the lung the capillaries are the major-site of vascular resistance.…”
Section: Resultsmentioning
confidence: 99%
“…11. 6,72,73,75,76 Recently, Burrowes et al 77 have begun to merge measurements providing detailed descriptions of the geometry of the large vessels obtained from volumetric CT, with statistically based models of the small-scale vascular structure. These studies have contributed significantly to the understanding of the flow distribution within the pulmonary circulation.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…Morphometric data have generally been obtained from plastic corrosion casts [60,63,66,67,68,76,79,82], and data obtained using imaging methods are becoming available [62,70,75]. The data consist of measurements of diameters lengths and numbers of vessels, and are commonly summarized by binning according to some ordering scheme [4,66,68].…”
Section: Morphometrymentioning
confidence: 99%
“…Human [67] Human [66] Dog [76] Dog [63] Cat [82] Rat [68] For a symmetrical bifurcating tree, B = 2; B increases above 2 as the tree becomes more asymmetrical [4]. Values of B obtainable from the pulmonary arterial morphmetric literature are also presented in Table 1.…”
mentioning
confidence: 99%